Après Sam: shaken or stirred? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Samuel Matsangaise was seeking international experience when he joined CTA as Publications Officer in 1997, after 5 years as scientific editor and then as Director at the University of Zimbabwe Press. It heightened his input to CTA, at a time when...